Peran Motivasi Kerja dalam Memediasi Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Pegawai di Dinas Ketahanan Pangan Kabupaten Penukal Abab Lematang Ilir - Feby Happy Monica; Djatmiko Noviantoro; Sari Samarina (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the role of work motivation in mediating the influence of transformational leadership style and organizational culture on employee performance at the Food Security Agency of Penukal Abab Lematang Ilir Regency. The research method used was a quantitative survey approach, employing a saturated sampling technique on the entire population of 46 employees. Data collection was conducted through closed-ended questionnaires, while data analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS application. The results showed that transformational leadership style had no effect on employee work motivation or performance. Organizational culture had a positive and significant effect on employee work motivation and performance. Work motivation had a positive and significant effect on employee performance. Furthermore, work motivation was shown to mediate the influence of organizational culture on employee performance, but not the influence of transformational leadership style on employee performance. The conclusion is that improving employee performance at the Food Security Agency of Penukal Abab Lematang Ilir Regency is more influenced by organizational culture and work motivation than by transformational leadership style.   Keywords: Transformational Leadership Style, Organizational Culture, Work Motivation, Employee Performance, SEM-PLS